Functional recovery of the adult murine hippocampus after cryopreservation by vitrification - Alexander German; Enes Yağız Akdaş; Cassandra Flügel-Koch; Ezgi Erterek; Renato Frischknecht; Anna Fejtova; Jürgen Winkler; Christian Alzheimer; Fang Zheng (Proceedings of the National Academy of Sciences, 2026)
Cryopreserving the adult brain is challenging due to damage from ice formation, and traditional freezing methods fail to maintain neural architecture and function. Vitrification offers a promising alternative but has not been surveyed in the brain. Here, we demonstrate short-term recovery of the adult murine hippocampus after vitrification of brain slices and of the whole brain in situ. Key features of the hippocampus are preserved, including structural integrity, metabolic responsiveness, neuronal excitability, and synaptic transmission and plasticity. Notably, hippocampal long-term potentiation (LTP) was well preserved, indicating that the cellular machinery of learning and memory remains operational. These findings extend known biophysical limits for cerebral hypothermic shutdown by demonstrating recovery after complete cessation of molecular mobility in the vitreous state and thus contribute to achieving the objective of structural and functional preservation of neural tissue.